(untitled) - Pearce, Craig L. (New York, 2010)
The Drucker Difference casts new light on Drucker’s business philosophy, analyzing his most important ideas in the context of today’s business world. Through individual contributions by professors from The Peter F. Drucker and Masatoshi Ito Graduate School of Management, it combines expert insight and current scholarship to reveal how organizations and executives can interpret and apply Drucker’s timeless ideas.
Keywords: Business,Industrial management,Leadership